A odisseia das águas: da teoria crítica à gestão hídrica pelo plantio, produção e conservação de água - Marques, Homel Pedrosa (2021)
The research aimed to identify and characterize the planting, production and water conservation projects implemented in the Atlantic Forest Biome of Minas Gerais and Espírito Santo in southeastern Brazil and in Catskills in New York in the United States, interrelating with the traditional and technical knowledge of the rural producers located in geographic territories where public policies for the management of water resources are implemented it. The inspiration for the conceptual bases and the theoretical framework adopted was based on timeless authors such as Thomas Khun and his reflections on Paradigm, as well as the reflection on Social Critical Theory of the Frankfurt School and on the School of Sociology of Knowledge by the Forte Program. The counterpoint of the authors and schools mentioned is confronted by Karl Popper's Falseability Theory. The method of study in multiple cases was used to research the projects: Conservador das Águas in Extrema-MG; Plantadores de Água in Alegre-ES; and the Catskills Watershed Corporation (CWC) in New York in the United States. The dissertation is characterized as qualitative research through participant observation techniques and through an ethnographic approach in the three case studies investigated in loco. The research was developed in four layers: 1) the theoretical magnifying glass, through bibliographical research; 2) the documental magnifying glass, through content analysis of institutional-legal records, maps and files that conceived the projects; 3) through the analytical listening of institutional actors, through scripted interviews recorded with the creators, formulators, managers and executors of the projects; and 4) by listening to rural producers and landowners, residents and tourists, through semi-structured interviews with project participants. Forty-nine interviews were conducted. The result presents a comparative table of findings and discoveries for the conservation of natural resources, guidelines to improve monitoring, expansion of communication, social participation and the governance arrangement implemented. The three researched projects have common aspects such as ecological sustainability, environmental education, and management of water resources in each territory and the challenges to overcome difficulties, for the continuous improvement necessary for the improvement of each project, considered forefront in environmental management both in Brazil and in the United States. Several outcomes point to more similarities than differences. The three projects develop actions for the revitalization of the watersheds.